Acetoxy-γ-valerolactone - Cameron Tristram (Acta Crystallographica Section E, 2013)
Levulinyl cellulose esters have been produced as an effective renewable binder for architectural coatings. The title compound, C7H10O4 (systematic name: 2-methyl-5-oxotetrahydrofuran-2-yl acetate), assigned as the esterifying species, was isolated and crystallized to confirm the structure. In the crystal, the molecules pack in layers parallel to (102) utilizing weak C—H...O interactions.